Criminal Law Enforcement Against Digital Financial Services Sector Companies for Misuse of Consumer Personal Data - Ananda Putri Nur Amalina; Sahat Maruli Tua Situmeang (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
This study aims to analyze criminal law enforcement against companies in the financial services sector for misusing consumers' personal data. The research method used is normative juridical, using both literature data which includes primary legal material in the form of applicable laws and regulations as well as secondary legal material in the form of scientific journal literature, books and other supporting sources and analyzed with a descriptive approach regarding the extent of sanctions imposed given as a result of misuse of personal data. The results of this study are criminal law provisions against companies in the financial services sector that misuse consumers' personal data are regulated in Law Number 27 of 2022 concerning Protection of Personal Data. Law enforcement against the protection of personal data by companies in the financial services sector requires legal political clarity from the current provisions. So it is necessary to take steps to optimize the application of criminal sanctions against companies in the financial services sector that misuse the personal data of their customers